1989
DOI: 10.1111/j.1472-8206.1989.tb00449.x
|View full text |Cite
|
Sign up to set email alerts
|

PREVENTION OF CCL4‐INDUCED LIVER CIRRHOSIS BY SILYMARIN

Abstract: The efficacy of silymarin treatment in preventing biochemical and histological alterations in CCL4-induced liver cirrhosis in rats was studied. Four groups of rats were treated with: (1) CCL4; (2) mineral oil; (3) CCL4 + silymarin; and (4) silymarin. All animals were sacrificed 72 h after the end of treatments. The activities of alkaline phosphatase (alk. phosp.), gamma-glutamyl transpeptidase (GGTP), glutamic pyruvic transaminase (GPT) and glucose-6-phosphatase (G6Pase), and bilirubin content were determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(76 citation statements)
references
References 29 publications
3
72
0
1
Order By: Relevance
“…Favari and Perez-Alvez reported that orally administered silymarin (50 mg/kg) to the rats with chronic carbon tetrachloride (CCl4) liver damage could reduce the collagen content in the liver of these animals up to 55% (increased with CCl4 approximately 4-to 6-fold as compared to controls) (Favari and Perez-Alvarez, 1997). In similar experiments, there was a reduction of collagen and pro-collagen III contents after biliary obstruction in the rat by 30% with 50 mg/kg/day although not at the level of 25 mg/kg/day of silymarin (Mourelle et al, 1989;Boigk et al, 1997). Silymarin suppressed the expression of pro-fibrogenic procollagen-α1(I) and TIMP-1 most likely via down-regulation of TGF-β1 mRNA in the rats with biliary fibrosis (Jia et al 2001).…”
Section: Antifibrotic Activitymentioning
confidence: 80%
“…Favari and Perez-Alvez reported that orally administered silymarin (50 mg/kg) to the rats with chronic carbon tetrachloride (CCl4) liver damage could reduce the collagen content in the liver of these animals up to 55% (increased with CCl4 approximately 4-to 6-fold as compared to controls) (Favari and Perez-Alvarez, 1997). In similar experiments, there was a reduction of collagen and pro-collagen III contents after biliary obstruction in the rat by 30% with 50 mg/kg/day although not at the level of 25 mg/kg/day of silymarin (Mourelle et al, 1989;Boigk et al, 1997). Silymarin suppressed the expression of pro-fibrogenic procollagen-α1(I) and TIMP-1 most likely via down-regulation of TGF-β1 mRNA in the rats with biliary fibrosis (Jia et al 2001).…”
Section: Antifibrotic Activitymentioning
confidence: 80%
“…In these investigations, such flavonoids reduced hepatocyte damage caused by administration of various chemicals including, among others, allyl alcohol (Miguez et al 1994), carbon tetrachloride (Mourelle et al 1989), halo-thane (Siegers et al 1983), acetaminophen (Muriel et al 1992) and phenylhydrazine (Valenzuela et al 1985). Several mechanisms of action were discussed: (1) stimulation of protein synthesis in the hepatocytes (Machicao & Sonnenbichler 1977), (2) radical scavenging and antioxidant properties (Ubeda et al 1995), (3) prevention of penetration of toxins into the cell (Münter et al 1986), and (4) inhibition of 5-lipoxygenase with reduced formation of leucotriens (Dehmlow et al 1996).…”
mentioning
confidence: 99%
“…CCl 4 causes liver necrosis, steatosis, degeneration of hepatocytes (44), and cirrhosis (7,45). CCl 4 was also found to precipitate apoptosis in the liver (46).…”
Section: Discussionmentioning
confidence: 99%